2013
DOI: 10.1103/physrevb.87.235105
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of the resistivity and charge-carrier sign in nanolaminated Ti2AlC: Experiment andab initiocalculations

Abstract: The anisotropy of Ti 2 AlC transport properties is investigated focusing on the Hall effect and resistivity vs temperature measurements performed on a highly (000l)-oriented thin film and a bulk polycrystalline sample. Experimental data are interpreted on the basis of density functional theory calculations including transport coefficients obtained with the Boltzmann semiclassical transport equation in the isotropic relaxation time approximation. It is shown that the Hall constant is independent of the temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 39 publications
4
19
0
Order By: Relevance
“…Subsequent transport work supported this idea [24]. Based on the preponderance of evidence to date, most researchers have concluded that indeed holes are the majority carriers in the basal planes [1,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent transport work supported this idea [24]. Based on the preponderance of evidence to date, most researchers have concluded that indeed holes are the majority carriers in the basal planes [1,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…[3] Additionally, the layered structure causes properties such as electrical conductivity to be anisotropic. [4] MAX phases are commonly synthesized using bulk methods such as pressureless sintering, hot pressing and reactive hot isostatic pressing. [5] Bulk methods yield polycrystalline samples of varying phase purities although phase pure samples are not uncommon.…”
mentioning
confidence: 99%
“…As the quality of sputtered films has progressively improved, work has started to focus on creating single crystal films for more detailed measurements of the intrinsic properties, initially most commonly with respect to conduction [4,16] but more recently also magnetism. [17][18][19][20][21] In order to realize the full potential of this family of inherently layered materials, the reproducibility and quality of samples have to be improved.…”
mentioning
confidence: 99%
“…Currently, the research efforts are directed towards, for example, 2D structures, such as graphene-like exfoliated MAX phase sheets (MXenes) [4][5][6], MAX phase nanotubes [7], manufacturing of freestanding structures [8], as well as understanding their optical [9,10], anisotropic [11][12][13], and magnetic [14][15][16][17][18][19] properties.…”
Section: Background To the Research Field Of The Thesismentioning
confidence: 99%